Mothers' Psychological Distress and Feeding of Their Preterm Infants. Issue 4 (July 2016) - Park, Jinhee; Thoyre, Suzanne; Estrem, Hayley; Pados, Britt F.; Knafl, George J.; Brandon, Debra
Abstract: Purpose: To examine the change in psychological distress of mothers of preterm infants and its association with maternal feeding behaviors as the infant transitions to full oral feeding. Study Design and Methods: This descriptive exploratory study used a subset of data from a study of the effects of a coregulated feeding intervention for 34 mothers and hospitalized preterm infants in a Level-III neonatal intensive care unit (NICU). Maternal psychological distress was measured by maternal worry (Child Health Worry Scale), depression (Center for Epidemiology-Depression Scale), and role stress (Parental Stress Scale: NICU-Role Alteration) at three time points: within 1 week prior to the first oral feeding (T1), and at achievement of half (T2) and full oral feeding (T3). Feedings were videotaped at T2 and T3. An observational coding system measured maternal feeding behaviors. Linear mixed modeling evaluated the change in maternal psychological distress and its association with mothers' feeding behaviors as the infant transitioned to full oral feeding. Results: Maternal depressive symptoms were highest at T1 and declined over time. Maternal worry and role stress were also highest at T1 but remained stable from T2 to T3. Increased maternal psychological distress, particularly depressive symptoms and role stress, were associated with less use of developmentally supportive feeding behaviors, that is, minimizing tactile stimulation, providing steady touch to contain or stabilize the infant, and regulating milk flow. Clinical Implications: Supporting maternal psychological well-being while infants are learning to feed orally may be an appropriate target for interventions to support mother–infant early feeding interactions. Abstract : Feeding a preterm infant can be stressful for mothers. This study evaluates changes in maternal psychological distress and its association with mothers' feeding behaviors as their preterm infants transitioned to full oral feeding. Nurses offering mothers of preterm infants emotional support may enhance maternal psychological well-being while their babies are learning to feed orally.